Evaluation of CADD Scores in Curated Mismatch Repair Gene Variants Yields a Model for Clinical Validation and Prioritization. Issue 7 (20th May 2015) - van der Velde, K. Joeri; Kuiper, Joël; Thompson, Bryony A.; Plazzer, John‐Paul; van Valkenhoef, Gert; de Haan, Mark; Jongbloed, Jan D.H.; Wijmenga, Cisca; de Koning, Tom J.; Abbott, Kristin M.; Sinke, Richard; Spurdle, Amanda B.; et al.
<x xml:space="preserve">Abstract</x> In silico estimation of pathogenicity is becoming a necessity to interpret the amount of variants produced by current high‐throughput DNA sequencing. Here we benchmark the promising new CADD method against a gold standard set of curated mismatch repair gene variants classified by the InSiGHT consortium and investigate any discrepancies we find.